The results and tolerance of concurrent chemoradiotherapy in patients with limited-stage small-cell lung cancer - Sas-Korczyńska, Beata; Skołyszewski, Jan; Małecki, Krzysztof; Pęcak, Magdalena; Korzeniowski, Stanisław (Contemporary Oncology/Współczesna Onkologia, 2002)
Application of concurrent chemoradiotherapy in patients with limited-stage small-cell lung cancer improves tumour control in thorax, overall and disease-free survival rates. Between 1994 and 2000 the group of 59 patients with limited-stage small-cell lung cancer received concurrent chemoradiotherapy at Radiotherapy Department of Oncology Centre in Kraków. The results of this method of treatment were presented. All patients received chemotherapy according to schedule PE (Cisplatin and Etoposid). At the same time the radiotherapy was applied. The irradiated volume contained primary tumour with margin and regional lymph nodes. The dose 45 Gy was delivered to this volume, and then a boost to the primary tumour of up 55 Gy was applied. The fraction dose was 1.8-2 Gy. Since 1995 thirty patients with complete response after treatment received prophylactic cranial irradiation. These patients received dose of 28-30 Gy in 2 Gy fractions. The results of treatment were estimated as respose of tumour after chemoradiotherapy, and rates of overall survival, and disease-free survival. The positive response after chemoradiotherapy was observed in 48 (81.4%) from which the complete response was achieved in 43 patients (72.9%). The overall survival rates were: 1-year - 66%, 2-years - 39.3%, and the disease-free survival rates were: 1-year - 55.5%, 2-years - 33.7%. The analysis of prognostic factors showed that complete response after treatment and prophylactic cranial irradiation had significant positive influence on results of treatment. During the follow-up the locoregional recurrece developed in 7 patients, observed progression of disese in 3 patients, and 32 patients developed distant metastases. The most frequent failure were brain metastases, which developed in 21 patients. We have demonstrated that probability of brain metastases occurrence was lower in patients with complete response, which received prophylactic cranila irradiation (7.1% at 6 months, 15.4% at 12 months, and 25.7% at 24 months after treatment) in comparison to patients which did not receive prophylactic cranial irradiation (51.9% at months, 61.5% at 12 and 24 months after treatment). The tolerance of concurrent chemoradiotherapy was estimated according to WHO scale. During chemoradiotherapy 32 patients developed mild (G1-2) hematological complications, and in 12 patients these complications were severe (G3 in 8 patients, and G4 in 4 patients). Seventeen patients developed oesophagitis (G1-2 in 13 patients, and G3-4 in 4 patients). Seventeen patients developed oesophagitis (Gl-2 in 13 patients, and G3-4 in 4 patients).